PERANCANGAN ALAT UKUR GAS HIDROKARBON (HC) DENGAN MENGGUNAKAN SENSOR MQ-4 BERBASIS MIKROKONTROLER AT89S52 - Putra Wibawa, I Nyoman Gede; Supardi, I Wayan; Putra Adnyana, I Gusti Agung (BULETIN FISIKA, 2016)
It has been designed a hydrocarbon gas measuring instrument using the sensor MQ-4. Gas levels were detected by the sensor is processed for display on seven segment through several circuits, the sensor circuit, comparator circuit, non-inverting amplifier cicuit, ADC0804 circuit, the minimum system microcontroller AT89S52, and a circuit of seven segment multiplexing. The entire circuit is powered by a power supply 5 VDC, -15 VDC and +15VDC. The measurement range of measuring instruments is ranging from 0 ppm to 131 ppm. The workings of this measuring instrument utilizes the characteristics of the sensor MQ-4 that has a change of output voltage proportional to the change of gas levels were detected. Comparator circuit is used to adjust the sensor output voltage to be 0 volts when measured 0 ppm HC gas. Because the change of the output voltage is small, that is 2 mV, it would require 10 times voltage gain to make the changes of the output voltage can be converted into digital data by the ADC0804, then the conversion result is sent to microcontroller. The data received by microcontroller AT89S52, then processed into the output levels of the gas that displayed on seven segment. Compatibility between measuring instrument and reference instrument were obtained from linear regression analysis of data from test the measuring instrument that is equal to 99,9%.